EVALUASI IMPLEMENTASI KEBIJAKAN MANAJEMEN RISIKO DALAM RANGKA MANAJEMEN KINERJA DI KEMENTRIAN KEUANGAN (2015) - Cahyadi, Hendra (JURNAL INFO ARTHA, 2015)
The purpose of this study is to evaluate the implementation of risk management policy at the Inspectorate General of the Ministry of Finance which has been implemented since 2008. The study was conduted with policy research approach. Secondary data of 2011 and 2012 were use. Interview conduted on 9 unit echelon II comprises 24 persons consisting of echelon 2, 3 and 4. Observations also made on to risk management agenda in the unit of echelon I and II.The result of the analysis and interpretation of the data showed that: (1) leadership commitment needed to support the implementation of policu especially in allocating resources more appropriately: (2) the process if umplementation of the policy needed to be put as a system rather than marely in administrative basic and these required knowledge development of the employees; (3) the mitigation activities needed to touched the causes of the risks and needed to encourage innovation in risks handling: (4) the achievement of organizatuinal goals neede to be more associated with risk management.The finding of study recommended to enhance socialization of risk management ,especially to the risk management administratice report and improve the educational training for all emplyee in administrative processes so it can be easily implemented. Improve the methodology for linking the organization with the achievement of the objectives of risk management. Encourage innovation in managing risks so risk management result are useful for the organization.